Multifunctional UHF RFID Analog Sensor System Using Energy-Oriented Sequential Estimation Algorithm - Zhang, Xu; Guo, Jing; Lin, Zhiyun; Li, Han-Xiong (IEEE transactions on instrumentation and measurement, 2025)
Ultrahigh frequency radio identification (UHF RFID) tags are widely used to provide passive and ubiquitous sensing with the competitive advantage of being low-cost. UHF RFID analog tag sensor system analyzes the features of backscattered signal, including RSSI and phase, to provide nearby environmental status of the RFID tag by eliminating the influences of measurement setup (relative distance and orientation between read/write device (RWD) and tag). In this article, a sequential estimation algorithm that accurately extracts two nearby environmental states (temperature and antenna-sensitive factors of transducer-integrated antennas, such as liquid levels in cylindrical glasses) of a self-tuning capable RFID tag while being robust to measurement setup variations. Our algorithm involves three key components: 1) collecting measurable parameters (RSSI, auto-tuned value (V) of self-tuning RFID chip, charging time, and persistent time) under a fixed measurement setup through radiated power adjustment to establish an offline dataset; 2) designing an energy-oriented fusion parameter that combines charging time and radiated power to effectively suppress measurement setup interference on temperature estimation; and 3) utilizing estimated temperature to filter offline data, followed by antenna-sensitive factor extraction through k-nearest neighbors (kNNs) analysis based on the closest k reference points in the filtered dataset. Experiments show that the proposed algorithm provides accurate temperature and liquid level information under different measurement setups. The proposed multifunctional UHF RFID analog sensor system obtains the ID, liquid level, and temperature from an RFID tag without any additional costs, which significantly expands the application range of RFID intelligent sensing.